The right to bear arms - Harris, Duchess (Harris, Duchess. American values and freedoms., 2018)
Explores the history and importance of Americans' Constitutional right to bear arms, and takes a balanced look at the controversies surrounding this right. Includes court cases, a glossary, resources for further information, and color photographs.